2017
DOI: 10.24953/turkjped.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Primary trimethylaminuria (fish odor syndrome) and hypothyroidism in an adolescent

Abstract: Primary trimethylaminuria (fish-odor syndrome) is a rare autosomal recessive inherited metabolic disorder due to decreased metabolism of trimethylamine by enzyme flavin-containing monooxygenase 3. We report an adolescent boy who was socially distressed with malodor and diagnosed trimethylaminuria by molecular analyses. The patient was previously found to have primary hypothyroidism at another center when he was being investigated for malodor. Our aim is to remind awareness of this rare, socially devastating me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, four functionally known amino-acid-substituted FMO3 variants, namely FMO3 p.Ser195Leu, p.Arg223Gln, and p.Ile441Thr [found in Japanese families (Shimizu et al, 2021b)] and FMO3 p.Asn61Ser [reported in European families (Dolphin et al, 2000)] were also found in the updated 38K JPN database. Among the 24 already known amino-acid substituted FMO3 variants, FMO3 p.Ile37Thr (Teresa et al, 2006) and p.Arg387His (Kilic, 2017) have been reported in the literature, but their catalytic function remains unknown. Seventeen synonymous FMO3 variants were also detected in this study:…”
Section: New Fmo3 Variantsmentioning
confidence: 99%
“…Moreover, four functionally known amino-acid-substituted FMO3 variants, namely FMO3 p.Ser195Leu, p.Arg223Gln, and p.Ile441Thr [found in Japanese families (Shimizu et al, 2021b)] and FMO3 p.Asn61Ser [reported in European families (Dolphin et al, 2000)] were also found in the updated 38K JPN database. Among the 24 already known amino-acid substituted FMO3 variants, FMO3 p.Ile37Thr (Teresa et al, 2006) and p.Arg387His (Kilic, 2017) have been reported in the literature, but their catalytic function remains unknown. Seventeen synonymous FMO3 variants were also detected in this study:…”
Section: New Fmo3 Variantsmentioning
confidence: 99%